Psikologi Pendidikan Islam Di Era Digital: Tantangan Dan Solusi - Rini Puspitasari; Mindani Mindani; Muhammad Farouk Alakbar Anshori; Melda Tri Aprisa; Junita Malasari; azizah Khoirunnisa (Irsyaduna: Jurnal Studi Kemahasiswaaan, 2025)
This study examines the challenges and solutions of Islamic educational psychology in the digital age, focusing on three core issues: digital distraction, exposure to negative content, and limited teacher digital literacy. Through qualitative literature review and thematic content analysis, the research identifies that gadget addiction and social media/gaming platforms disrupt students' learning focus, moral development, and mental health, contradicting Islamic principles like the preservation of al-'aql (intellect). Educators' unpreparedness to integrate technology with Islamic values further hinders faith-based learning effectiveness. Proposed solutions include: (1) Developing Islamic-based technological platforms (e.g., "TafsirAI") integrating Quran-Hadith content with TPACK (Technological Pedagogical Content Knowledge) frameworks; (2) Digital moral education via creative media (e.g., animated Prophet stories) to enhance intrinsic motivation grounded in ihsan (excellence); and (3) Multisector collaboration (education institutions-digital platforms) to filter harmful content. These strategies aim to balance technological advancement with Islamic values, fostering academically proficient, digitally resilient, and ethically grounded students. The study underscores the need for holistic approaches to digital disruption, while acknowledging limitations in sample scope and calling for further research across diverse educational levels.